Lapatinib plus capecitabine for HER2-positive advanced breast cancer: a multicentre study of Anatolian Society of Medical Oncology (ASMO) - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2014)
Lapatinib is the first dual tyrosine kinase inhibitor of human epidermal growth factor receptor type 2 (HER2/neu) and epidermal growth factor receptor (EGFR). The present study evaluated the efficacy and tolerability of the combination of lapatinib and capecitabine in patients with metastatic breast cancer (MBC) who progressed after therapy with trastuzumab, a taxane and/or anthracycline. A total of 203 patients with a median age of 48 years (range: 25-82 years) were evaluated retrospectively in 11 centres between September 2007 and May 2011. All the patients had HER2-positive MBC progressing after trastuzumab and chemotherapy including an anthracycline and/or taxane. All patients were treated with the combination of lapatinib (1250 mg/day, continuously) and capecitabine (2000 mg/m(2) on days 1 through 14 of a 21-day cycle). Data on demographics, clinical outcome, and toxicity were collected for descriptive analyses. The median follow-up was 10.7 months (range: 1-40 months). An overall response rate (ORR) of 33.4% was achieved including 7 complete responses (CR, 3.4%), 61 partial responses (PR, 30.0%), and 44 stable disease (37.9%). Clinical benefit rate of 71.3% was achieved. Median progression-free survival (PFS) was 7 months (95% CI: 6-10 months), with a median overall survival (OS) of 15 months (95% CI: 12-18 months). The most common side effects were hand-foot syndrome (46.8%), nausea (42.3%), fatigue (42.2%), anorexia (38.5%), diarrhea (31.5%), and rash (29.6%). Grade 3-4 toxicities were identified as hand foot syndrome (7.9%), diarrhea (6.9%), fatigue (5.9%), and rash (5.4%). There were no symptomatic cardiac events. Lapatinib and capecitabine combination therapy is effective and well tolerated in patients with MBC who had progressive disease after trastuzumab, taxane, and/or anthracycline therapy, as evidenced by this retrospective evaluation. Toxicity was mild to moderate with low grade 3-4 toxicity.
Keywords: Advanced breast cancer; Lapatinib; Capecitabine; HER2; ADJUVANT CHEMOTHERAPY; MONOCLONAL-ANTIBODY; 1ST-LINE TREATMENT; TRASTUZUMAB; EFFICACY; SAFETY; METASTASES; SURVIVAL; THERAPY; WOMEN